2013
DOI: 10.1002/jmv.23581
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C virus infection among hemodialysis patients in yogyakarta, Indonesia: Prevalence and molecular evidence for nosocomial transmission

Abstract: Hemodialysis patients are at an increased risk of acquiring hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. However, the prevalence of hepatitis viral infection and its genotype distribution among hemodialysis patients in Indonesia are unclear. In order to investigate these issues and the possibility of nosocomial transmission, 161 hemodialysis patients and 35 staff members at one of the hemodialysis unit in Yogyakarta, Indonesia, were tested for serological and virological markers of both virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 64 publications
3
21
1
Order By: Relevance
“…Our previous report revealed that >90z of samples obtained from the general population, chronic liver disease patients, and patients on maintenance hemodialysis in Surabaya belong to the genotype B and subtype adw (13); this finding is similar to the results found in other parts of Java Island (10,25), and the genotype/ subtype C/adrq + was mostly found in the most eastern region of Indonesia (in the Papuan ethnic group) (9,25,28). This study showed at least 30z of the samples (3/9) were of C/adrq + , and 2 of them were from Maduranese individuals.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Our previous report revealed that >90z of samples obtained from the general population, chronic liver disease patients, and patients on maintenance hemodialysis in Surabaya belong to the genotype B and subtype adw (13); this finding is similar to the results found in other parts of Java Island (10,25), and the genotype/ subtype C/adrq + was mostly found in the most eastern region of Indonesia (in the Papuan ethnic group) (9,25,28). This study showed at least 30z of the samples (3/9) were of C/adrq + , and 2 of them were from Maduranese individuals.…”
supporting
confidence: 81%
“…HBV isolates of different genotypes and subtypes show different geographical distributions, virological characteristics, and possibly, clinical outcomes (9,10). Genotypes B and C (HBV/B and HBV/C, respectively) are predominant in Asia and particularly, in Indonesia (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis is being decentralized across Vietnam into district and provincial centers where adherence to infection prevention and control policy and guidelines associated with HBV and HCV may be suboptimal. 39 Yet, our national pooled HBV and HBV and HCV coinfection rates were higher than rates in low-resource regions outside Asia, such as Libya where the rates were lower for HBV (2.6%, 95% CI 2-3.3%) and HBV and HCV coinfection (1.2%, 95% CI 0.9-1.7%). [34][35][36][37] The move away from anti-HCV toward HCV-coreAg screening is based on the need for accuracy, with experts suggesting that, while the nucleic acid testing (NAT) technique is superior to anti-HCV, it should be replaced with HCV-coreAg for routine monitoring of chronic hemodialysis patients because HCV-coreAg is more cost-effective, less labor-intensive, and comparable for accuracy.…”
Section: Discussionmentioning
confidence: 77%
“…22 Several studies have also been performed in Indonesia, studies were conduct in West Java and Yogyakarta, they report that the prevalence of HBV infection in HD patient were 6.8% and 11.2%. 13,14 Some countries have different policies regarding blood transfusions and the use of special machines HD in patients with HBV infection are becoming some factors that in uence in the transmission of HBV. In some developed countries, precautions HBV infection during blood donation and when initation of HD might have been better than the developing countries.…”
Section: Discussionmentioning
confidence: 99%